Job Satisfaction Bridges Contract Violation and Turnover Intention - Priyatmika, Risma Ayu; Kurniawan, Ignatius Soni; Kusuma, Nala Tri (LifeSciFi, 2025)
Employee retention is a critical challenge in public sector organizations, where unmet expectations and organizational misalignments can influence workforce stability. Psychological contract violations, perceived breaches of unwritten organizational promises, have been linked to decreased job satisfaction and increased turnover intentions. However, limited empirical studies examine the mediating role of job satisfaction in this relationship within public institutions. This study aims to investigate how psychological contract violation affects turnover intention and whether job satisfaction mediates this effect. Quantitative research was conducted using a survey of 70 employees, with data analyzed through Partial Least Squares-Structural Equation Modeling (PLS-SEM) using SmartPLS. Results indicate that psychological contract violations significantly reduce job satisfaction and increase turnover intentions. Job satisfaction negatively affects turnover intentions and partially mediates the relationship between contract violation and intention to leave. These findings highlight the importance of aligning organizational promises with employee expectations. Implications suggest that public institutions should enhance communication, implement clear policies, and provide career development opportunities to strengthen employee satisfaction and retention.